Lead isotope provinciality of central North Pacific Deep Water over the Cenozoic. (17th May 2013) - Chen, Tian‐Yu; Ling, Hong‐Fei; Hu, Rong; Frank, Martin; Jiang, Shao‐Yong
Abstract: [1] Understanding the pre‐anthropogenic Pb cycle of central North Pacific deep water has attracted a lot of attention in recent years, partly because of its unique geographical location in that it is a remote gyre system characterized by high dust fluxes and sluggish overturning circulation. However, the factors controlling Pb isotope evolution in this area over the Cenozoic are still controversial and various mechanisms have been proposed in previous studies. Here we report new Pb and Nd isotope time series of four ferromanganese crusts (two from the western Pacific near the Mariana arc and the other two from the central Pacific). Together with previously published records, we discuss for the first time the significance of a persistent and systematic Pb isotopic provinciality recorded by central North Pacific crusts over the Cenozoic. We propose that globally well mixed stratosphere volcanic aerosols could contribute Pb but have not been the major factors controlling the Pb isotope distribution in the central North Pacific over time. Island arc input (and probably enhanced hydrothermal input between about 45 and 20 Ma) likely controlled the Pb isotope provinciality and evolution prior to 20 Ma, when coeval Pb isotope records in different crusts showed large differences and atmospheric silicate dust flux was extremely low. After the Eocene, in particular after 20 Ma, Asian dust input has become an isotopically resolvable source, while island arc‐derived Pb has remained important to balance the dust input and to produce the observed Pb isotope distribution in the central North Pacific during this period. Key Points: A detailed picture of Pb isotope evolution of deep central Pacific is obtained Systematic Pb isotope provinciality over the Cenozoic is revealed Pb isotopes are sensitive to local input even in remote oceanic gyre system